Character Study Strengthening the Heart of Good Leadership - Klann, Gene; Klann, Gene (Center for Creative Leadership, 2003)
In the past few years, headlines in the business pages have underscored the fact that some corporate leaders leave a lot to be desired in the area of character. Yet because it is subjective and controversial, the issue of character has largely been left out of the equation when it comes to training and preparing leaders. If undertaken with the right perspective, however, there are ways to develop character in leaders.